Non-Test Evaluation Framework Using the ADDIE Model to Enhance the Quality of Islamic Religious Education Learning - Ahmad Firdaus Al Amien; Zahra Aflaha Farhani; Ahsari Fadli Siregar; Muhammad Fahmi Setiawan; Nabhan Halim Al Azhar; Romelah Romelah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Islamic Religious Education (PAI) evaluation at the junior secondary level remains dominated by cognitive-based written tests, leaving students' affective and psychomotor achievements inadequately measured. This study aims to analyze the development process and evaluate the effectiveness of a non-test evaluation model based on the ADDIE framework in enhancing PAI learning quality at the junior secondary level. A qualitative case study approach was employed at one public junior high school. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model. Results indicate that the five ADDIE stages produced a systematic non-test evaluation syntax with supporting instruments comprising interview guidelines, assessment rubrics, and observation sheets, implemented through a responsive-objective-constructive principle of teacher reaction. The model improved students' psychomotor skills and attitudes of discipline, responsibility, and cooperation, while fostering a more collaborative school culture. This study offers an applicable non-test evaluation model for PAI teachers and enriches scholarship on integrating instructional design with authentic, character-based assessment.